A reconstructed human skin model containing macrophages to set up a delayed wound healing model of cutaneous leishmaniasis - Schilrreff, Priscila (2019)
Cutaneous leishmaniasis (CL) is a vector-borne neglected disease caused by protozoan parasites of the genus Leishmania. Disfiguring and socially stigmatizing skin lesions develop at the bite site of the parasite-infected female sand fly [1]. Tissue damage and disease in CL are primarily caused by an excessive host immune response against the intracellular infection of dermal macrophages [2]. The dermal lesions persist for months or even years, but eventually heal on their own [3]. Treatment of CL is problematic, as long series of painful injections with the toxic pentavalent antimonials remain the standard therapy [1] and lesions are left alone to self-cure with the risk of secondary bacterial or fungal infection. New therapies for CL and CL lesions are urgently needed. Therefore, realistic CL lesion models are essential as a predictive experimental platform to identify more effective topical strategies. To that aim we integrated for the first time in vitro-generated M1 polarized macrophages differentiated from the human monocytic THP‐1 cell line into reconstructed human skin (RHS). THP-1 derived macrophages were localized in the RHS dermal compartment and distributed homogenously in accordance with native human skin. Standardized circular wounds were made with a 18 gauge blunt tip needle or by punch biopsy. In order to impair wound healing, wounded RHS was stimulated with intradermal application (for needles) or drops (for punch wounds) of IFN-γ in combination with LPS and/or hydrocortisone. Wound healing was monitored on days 1, 3 and 7 after wounding by histological examination of RHS. Immunohistochemical (Ki67, K14, tenascin-C, laminin 5, α‐SMA) and pro-inflamma ory cytokine analyses were performed pre‐ and post‐skin wound and stimulation, to increase the characterization of the model and to assess the effects of IFN-γ, LPS and hydrocortisone in wound healing RHS models. Early in healing, IFN-γ-LPS-hydrocortisone wounds displayed reduced proliferation and re-epithelialisation and heightened inf lammatory response compared with control wounds. H&Estained sections showed increased epidermal thickness and a lack of dermal epidermal junction in the wound zone. In summary, we integrated functional THP-1 derived macrophages into RHS and induced a delayed wound healing to provide a unique experimental test platform to evaluate the effects of new topical treatments.